(untitled) (European Bison Conservation Newsletter, 2019)
The year 2019 marks the very special 90th anniversary of the restitution of European bison in its Białowieża “lair”. It was in Białowieża, 10 years after the last wild wisent was eradicated, that the due restitution in the historic refuge of European bison in the Białowieża National Park commenced. But we could not admire the free-roaming wisents in the Białowieska Forest (and in many other places in Poland and in the world) today if it had not been for the 4 European bison from Białowieża (back when the Białowieża Forest still sheltered 724 individuals) that were transferred and successfully restituted in 1865 in the woods of Pszczyna at the initiative of Prince Hans Heinrich XI von Hochberg. In the restitution process of the free-range European bison in the Białowieska Forest participated the descendants of the 4 animals transferred from Białowieża to Murcki, Upper Silesia. The descendants played a great role in the restitution of wisents in the Białowieska Forest in the years 1929–1966 and in preserving the species from total extinction. While in 1919 no free-ranging European bison could be found anymore in Białowieża, in the woods of Pszczyna there were still 47 (13.34) individuals of a subspecies of lowland wisent. When the restitution of European bison in the Białowieska Forest began in 1929, the Pszczyna herd counted only 7 (4.3) specimens bred in a semi-free system. Nine out of 11 animals from the Pszczyna lineage, transferred to Białowieża in the years 1936–1957, participated in the forming and restitution of the Białowieża herd. Their progeny were 85 (41.44) calves. A prominent role in the restitution process was played by the bull M 229 Plisch. His offspring, from the cows Biscaya and Biserta, began the effective revival of the Białowieża herd. Plisch was a strong sire – his legacy was 48 calves born by 15 different cows. Plisch is considered the progenitor of almost all wisent living in the Białowieska Forest.